Lipid peroxidation: from basic mechanisms to clinical relevance - Morrow, Jason (Henry Stewart Talks, 2007)
Oxidant stress, lipid peroxidation and related terms, Basic mechanisms of lipid peroxidation and relevance to human physiology and pathophysiology, Methods to quantify oxidative stress and lipid peroxidation, F2-Isoprostanes (F2-IsoPs) as indices of oxidant stress in vivo, Role as markers in human physiology and pathophysiology, Effects of interventions on IsoP formation, Advantages and disadvantages of isoprostane quantification
Archived at 2018/05/31